MRI demonstrates a decrease in myocardial infarct healing and increase in compensatory ventricular hypertrophy following mechanical microvascular obstruction. Issue 4 (22nd January 2014) - Bajwa, Hisham Z.; Do, Loi; Suhail, Mohammed; Hetts, Steven W.; Wilson, Mark W.; Saeed, Maythem
<x xml:space="preserve">Abstract</x> Purpose To provide direct evidence that mechanical obstruction of microvessels inhibits infarct resorption (healing) and enhances left ventricular (LV) remodeling using MRI. Materials and Methods Animals (n = 20 pigs) served as controls (group I) or were subjected to either 90 min left anterior descending (LAD) coronary artery occlusion/reperfusion (group II) or 90 min LAD occlusion/ microemboli delivery/reperfusion (group III). MRI (cine and delayed contrast enhanced MRI, DE‐MRI) was performed at 3 days and 5 weeks after interventions and used for assessing LV function, mass, and extent of myocardial damage and microvascular obstruction (MVO) using semi‐automated threshold method. Results Persistent MVO in the core of contiguous infarct was larger and more frequent (n = 8/8) in group III than group II (4/8) on DE‐MRI at 3 days. Furthermore, patchy microinfarct, as a result of microembolization, was visible as hyperenhanced zone at the borders of the contiguous infarct. The reduction in ejection fraction and increase in LV volumes on cine MRI were greater in group III than group II at 3 days and 5 weeks, which may be attributed to the slow infarct resorption, MVO extents and patchy microinfarct at the borders. Conclusion This MRI study illustrates the recently raised conjecture that MVO delays/inhibits infarct resorption (healing), accentuates LV hypertrophy and pathological remodeling. J. Magn. Reson. Imaging 2014;40:906–914. © 2014 Wiley Periodicals, Inc.